Forging the collective memory : government and international historians through two World Wars - Wilson, Keith M. (Keith Malcolm), 1944- (Berghahn Books, 1996)
"When studying the origins of the First World War, scholars have relied heavily on the series of key diplomatic documents published by the governments of both the defeated and the victorious powers in the 1920s and 1930s. However, this volume shows that these publications, rather than dealing objectively with the past, were used by the different governments to project an interpretation of the origins of the Great War that was more palatable for them and their country than the truth might have been. In revealing the policies that influenced the publication of the documents, the relationships between the commissioning governments, their officials, and the historians involved, this collection serves as a warning that even seemingly objective sources have to be used with caution in historical research."--